OCORRÃŠNCIA DE ð˜šð˜µð˜³ð˜¶ð˜µð˜©ð˜¢ð˜¯ð˜µð˜©ð˜¶ð˜´ ð˜·ð˜¶ð˜ð˜¨ð˜¢ð˜³ð˜ªð˜´ MART., ð˜šð˜µð˜³ð˜¶ð˜µð˜©ð˜¢ð˜¯ð˜µð˜©ð˜¶ð˜´ ð˜¤ð˜°ð˜¯ð˜¤ð˜ªð˜¯ð˜¯ð˜¶ð˜´ MART., ð˜—ð˜©ð˜°ð˜³ð˜¢ð˜¥ð˜¦ð˜¯ð˜¥ð˜³ð˜°ð˜¯ ð˜³ð˜¶ð˜£ð˜³ð˜¶ð˜® (L) GRIS. E ð˜—ð˜©ð˜°ð˜³ð˜¢ð˜¥ð˜¦ð˜¯ð˜¥ð˜³ð˜°ð˜¯ ð˜ð˜ªð˜¯ð˜¦ð˜¢ð˜³ð˜ªð˜§ð˜°ð˜ð˜ªð˜¶ð˜® EICHL. E SEUS HOSPEDEIROS NO PARQUE DA ESCOLA SUPERIOR DE AGRICULTURA â€œLUIZ DE QUEIROZâ€ - Rochelle, Luiz Antonio; Almeida, MarcÃlio de (REVISTA DE AGRICULTURA, 2020)
OCORRÃŠNCIA DE ð˜šð˜µð˜³ð˜¶ð˜µð˜©ð˜¢ð˜¯ð˜µð˜©ð˜¶ð˜´ ð˜·ð˜¶ð˜ð˜¨ð˜¢ð˜³ð˜ªð˜´ MART., ð˜šð˜µð˜³ð˜¶ð˜µð˜©ð˜¢ð˜¯ð˜µð˜©ð˜¶ð˜´ ð˜¤ð˜°ð˜¯ð˜¤ð˜ªð˜¯ð˜¯ð˜¶ð˜´ MART., ð˜—ð˜©ð˜°ð˜³ð˜¢ð˜¥ð˜¦ð˜¯ð˜¥ð˜³ð˜°ð˜¯ ð˜³ð˜¶ð˜£ð˜³ð˜¶ð˜® (L) GRIS. E ð˜—ð˜©ð˜°ð˜³ð˜¢ð˜¥ð˜¦ð˜¯ð˜¥ð˜³ð˜°ð˜¯ ð˜ð˜ªð˜¯ð˜¦ð˜¢ð˜³ð˜ªð˜§ð˜°ð˜ð˜ªð˜¶ð˜® EICHL. E SEUS HOSPEDEIROS NO PARQUE DA ESCOLA SUPERIOR DE AGRICULTURA â€œLUIZ DE QUEIROZâ€